Broken Boundaries : Women and Feminism in Restoration Drama - Quinsey, Katherine M., 1955- (Book collections on Project MUSE., 1996)
This volume of twelve original essays is the first comprehensive study of feminist issues in Restoration drama. The late seventeenth century marks a pivotal era in the history of feminism, when Renaissance assumptions about gender and patriarchy were being directly challenged. For the first time, women appeared onstage as actresses, made their presence felt as spectators and patrons, and wrote a number of the plays produced in theaters. In an unusually direct and probing way, drama of the Restoration period raised radical questions about the place of women in the family and in society, and abo.